2020
DOI: 10.1123/ijspp.2019-0165
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of In-Season, Low-Volume Sprint Interval Training With and Without Sport-Specific Actions on the Physical Characteristics of Elite Academy Rugby League Players

Abstract: Purpose: To determine the utility of running-only and rugby-specific, in-season sprint interval interventions in professional rugby league players. Methods: Thirty-one professional academy rugby players were assigned to a rugby-specific (SITr/s, n = 16) or running-only (SITr, n = 15) sprint interval training group. Measures of speed, power, change of direction ability, prone Yo-Yo Intermittent Recovery Test (Yo-Yo IR1) performance, and heart rate recovery were taken before and after the 2-week intervention as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Focus on the offseason might prove beneficial and be used an opportunity to further develop players whilst allowing sufficient recovery. 3 For example, several researchers have demonstrated that short-duration interventions consisting of sprint interval, 18 repeated sprint 8 and/or speed and agility sessions 19 across a 2-4-week period are effective for improving linear sprint performance and may be considered by coaches as a simply and efficient modality of training. Furthermore, the inclusion weight-based, plyometric or sled training is also reported to improve or at least maintain linear sprint performance in soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…Focus on the offseason might prove beneficial and be used an opportunity to further develop players whilst allowing sufficient recovery. 3 For example, several researchers have demonstrated that short-duration interventions consisting of sprint interval, 18 repeated sprint 8 and/or speed and agility sessions 19 across a 2-4-week period are effective for improving linear sprint performance and may be considered by coaches as a simply and efficient modality of training. Furthermore, the inclusion weight-based, plyometric or sled training is also reported to improve or at least maintain linear sprint performance in soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate recovery can be defined as the rate at which HR declines after exercise cessation [10,39] and may be collected with athletes lying supine [123], sitting upright [12,45], standing [89,121], or walking [95]. Similarly, HRR can be assessed as the absolute (HRR[d]) [45,47,48,53,54,57,59,61,66,88,100,103,107,114,119,121,123,124] or relative (HRR[%d]) [12,47,53,60,66,102,104,107,113,114,121] difference between HRex and HR value observed between 10 and 180 s post-test. Alternative approaches include the actual HR value observed at the end of the designated recovery period in absolute (HRR[a]) [66,74,89,95,99,121,125] or relative (HRR[%]) [66,89,…”
Section: Hr Recoverymentioning
confidence: 99%
“…Runners and RL players with greater running economy have previously demonstrated lower energy expenditures, particularly as running speeds and muscular fatigue increase. 11,26 Furthermore, repeated exposure to high intensity interval training has been shown to increase muscle pain tolerance. 27 As RL players are repeatedly exposed to high intensity interval training, this increased tolerance may allow players to sustain high intensity output over a longer time frame, thus attaining a higher score on the Yo-Yo IR2 test.…”
Section: Discussionmentioning
confidence: 99%
“…recently reported the training loads (TLs) across various domains during a two-week, in-season period with the result suggesting a standard programme for all players. 11 Therefore, when applied to developing junior elite athletes, the aforementioned model may, in part, contribute to understanding the varied responses to similar training programmes at particular developmental levels. In turn, and if correct, the model could provide a foundation for more individualised training programming, as opposed to the generalised physiological programming often utilised in developmental stage RL programmes.…”
Section: Introductionmentioning
confidence: 99%